Peningkatan Memahami Teks Persuasif Melalui Model Discovery Learning Siswa Kelas VIII SMP Muhammadiyah 02 Kota Malang - Suriyanto, Suriyanto; Wardoyo, Hadi; Halim, M. Amirul (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this study is to describe the application of the discovery learning learning model to improve the understanding of persuasive text content of students of SMP Muhammadiyah 02 Malang City and to find out the increase in understanding of persuasive text content through the discovery learning model in grade VIII SMP Muhammadiyah 02 Malang City. This type of research is Classroom Action Research (PTK) with a qualitative approach. This class action research is carried out in two cycles. Each cycle consists of planning, execution, observation and reflection. The subjects of this study were grade VIII students of SMP Muhammadiyah 02 Malang City in the even semester of the 2022/2023 academic year, totaling 16 students. The data used include the results of cycle tests for each action, observations of learning activities, interview results, field notes. Data analysis used in this research is: data reduction, data presentation, conclusion drawing and verification. The success rate of learning in the classroom with learning achievement based on the implementation of the prestest and posttest of 16 students is categorized as quite active, evidenced by 56.10% in cycle I and 81.66% in cycle II, an increase in pretest by 25%.  Furthermore, by 57.76% in cycle I and 90% in cycle II, there was an increase in posttest by 33%. Based on the results of the study, it can be concluded that discovery learning can improve the understanding of the concept of grade VIII students of SMP Muhammadiyah 02 Malang City.